Pengaruh kecerdasan emosional terhadap communication apprehension saat proses belajar siswa - Muslimah, Dian; Tobing, Christine Masada Hirashita; Wulansari, Lusiana (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the purpose of this research is to find out whether or not there is an effect of Emotional Intelligence on Communication Apprehension during the Learning Process. This research is quantitative research. The population of this study was 244 residents of MA Al-Khairiyah Jakarta and the research sample was 69 students who were divided into 2 groups, namely in the experimental group (class XI MIPA) which would be given treatment in the form of sociodrama group guidance services as many as 35 students and in the control group (class XI IPS) which did not give treatment using sociodrama group guidance services as many as 34 students. Sampling using purposive sampling technique. Data were analyzed by paired sample t test. The results of the independent t-test of the two variables shows that the significance value (2-tailed) is 0.00 < 0.05 because the value of 0.00 < 0.05, it can be concluded that H1 is accepted and H0 is rejected. This shows an increase in emotional intelligence and a decrease in communication apprehension in class XI MIPA students after being given sociodrama group guidance services.